Pengaruh Stimulasi Motorik Halus terhadap Kemampuan Menulis Permulaan Anak Usia 5-6 Tahun - Usman; Arismunandar; Sadaruddin; Syamsuardi; Hasmawaty; Hajerah (NANAEKE: Indonesian Journal of Early Childhood Education, 2023)
This study aims to determine the effect of delicate motor stimulation on improving children’s ability to write letters by combining straight lines, flat lines, right-left oblique, left curves, right curves, and upper and lower curves into letters. The study used a quantitative approach, with one group pretest and posttest experimental methods. The study sample was 20 people. Data is collected through observation sheets by providing a checklist of aspects achieved by students. A paired sample t-test is used to analyze the data. The results of data analysis showed that the activities of drawing straight lines, flat lines, right left tilts, left curves, right curves, upper arches, and lower curves increased children’s initial writing skills in forming the alphabet